A Complementary Therapy with Trigonella foenum-graecum L. and Citrullus colocynthis (L.) in Type 2 Diabetes Mellitus: A Double-Blind Randomized Controlled Clinical Trial - Babak Pezeshki; Seyed Mohammadreza Torabi; Massih Sedigh Rahimabadi; Hossein Pourmontaseri; Foroogh Namjoyan; Mohammad Hossein Dabbaghmanesh; Elham Zarenezhad; Mehdi Sharafi; Mahsa rostami chijan (Fasa University of Medical Sciences, 2024)
Background & Objectives: Diabetes is a known chronic disease affecting more than 400 million people and causing millions of deaths worldwide annually. The World Health Organization predicts that by 2030, diabetes will become the seventh leading cause of death. In the last decades, numerous chemotherapy approaches have been used. However, herbal remedies have accounted for more than 70 percent of the total administered antidiabetic treatments during the last decade. In this study, we aimed to develop a novel natural antidiabetic therapy with Trigonella foenum-graecum (T. foenum-graecum) L. and Citrullus colocynthis (C. colocynthis) (L.). Based on past studies, using C. colocynthis singly can cause diarrhea, abdominal pain, and heartburn, hence in order to reduce these complications, we applied this plant in combination with T. foenum-graecum based on the recommendations of Persian medicine references. Materials & Methods: We admitted 34 diabetics aged 30-65 years old to design a double-blind parallel randomized controlled clinical trial. We prepared therapeutic capsules containing a combination of 40 mg of C. colocynthis and 350 mg of T. foenum-graecum L. We divided participants into an interventional (n=17) and placebo (n=17) groups and measured fasting blood sugar (FBS) levels, lipid profile, and liver function tests initially. After two weeks, all participants returned for a visit, and FBS and blood sugar (BS) were measured. At the end (12th week), all outcomes were measured and analyzed using an independent t-test and Chi-squared (χ2). Results: The FBS levels decreased significantly in the intervention group compared to that of the control group (171.8±54.9 versus 149.6±46.4, p=0.024), but the improvements in the lipid profile and liver function were not statistically significant. Conclusion: This study unveiled that combination of T. foenum-graecum L. and C. colocynthis L. at safe levels significantly decreased the FBS levels among T2DM patients. Further studies are needed to provide more efficient antidiabetic effects with the low side effects.